Right ventricular functional recovery after acute myocardial infarction: relation with left ventricular function and interventricular septum motion. GISSI-3 echo substudy. Issue 4 (16th March 2005) - Popescu, B A; Antonini-Canterin, F; Temporelli, P L; Giannuzzi, P; Bosimini, E; Gentile, F; Maggioni, A P; Tavazzi, L; Piazza, R; Ascione, L; Stoian, I; Cervesato, E; et al.
Abstract : Objective: To evaluate the pattern of right ventricular (RV) functional recovery and its relation with left ventricular (LV) function and interventricular septal (IVS) motion in low risk patients after acute myocardial infarction (AMI). Design and setting: Multicentre clinical trial carried out in 47 Italian coronary care units. Patients: 500 patients from the GISSI (Gruppo Italiano per lo Studio della Sopravvivenza nell'Infarto Miocardico) -3 echo substudy, who underwent serial echocardiograms 24–48 hours after symptom onset and at discharge, six weeks, and six months after AMI. Results: Tricuspid annular plane systolic excursion (TAPSE) increased significantly during follow up (mean (SD) 1.79 (0.46) cm at 24–48 hours to 1.92 (0.46) cm at six months, p < 0.001) and the increase was already significant at discharge (1.88 (0.47) cm, p < 0.001). LV ejection fraction (LVEF) was the best correlate of TAPSE at 24–48 hours ( r = 0.15, p = 0.001). TAPSE increased significantly in patients both with reduced (< 45%) and with preserved (⩾ 45%) LVEF, but the magnitude of increase was higher in patients with lower initial LVEF (p = 0.001). Improvement in IVS wall motion score index (IVS-WMSI) was the only independent predictor of TAPSE changes during follow up ( r = −0.12, p = 0.007). Conclusions: In low risk patients after AMI, RV function recovered throughout six months of follow up and was already significant at discharge. TAPSE was significantly related to LVEF at 24–48 hours. The magnitude of RV functional recovery was higher in patients with lower initial LVEF. RV functional recovery is best related to IVS-WMSI improvement, suggesting that IVS motion has an important role in RV functional improvement in this setting.